Fabrication and characterization of semi-refined carrageenan films incorporated with TiO2 nanoparticles - Khadijah Husna, Abd Hamid; Jayakumar, Tarchiani; Gunasegaran, Sarmeswari; Nurul Aini, Mohd Azman (Universiti Malaysia Pahang, 2023)
In this study, a packaging film was developed using semi-refined carrageenan, incorporating varying concentrations of TiO2 nanoparticles. The aim of this study was to investigate the effect of TiO2 nanoparticles on the properties of the SRC-based film. The films were prepared through a casting method, and the resulting samples were characterized in terms of their functional, mechanical, and physical properties. The SRC film containing 1 wt% of TiO2 nanoparticles demonstrated the highest tensile strength. However, with the addition of TiO2 nanoparticles at any concentration (1, 3, 5, and 7 wt%), the elongation at break of the SRC film decreased in comparison to the SRC film without TiO2 nanoparticles. Moreover, as the concentration of TiO2 nanoparticles increased from 1 to 7 wt%, the moisture content, and water solubility of the SRC films decreased. The FTIR spectra analysis provided valuable information on the interaction between SRC and TiO2 nanoparticles. The results suggest that incorporating TiO2 nanoparticles into semi-refined carrageenan films shows promise for developing packaging materials with improved mechanical strength and physical performance.